EFFECT OF A COMMUNITY-BASED PARTICIPATORY EDUCATION PROGRAMME ON PARTICIPANTS’ KNOWLEDGE OF AND ATTITUDE TO HUMAN TRAFFICKING IN OYO AND OSUN STATES, NIGERIA (2015)
Human trafficking, a social menace that involves the recruitment, transfer and harbouring of persons is a fast growing organised crime globally with Nigeria stigmatized as a country of origin, transit and destination. Regardless of efforts towards stemming the tide of human trafficking, the menace still persists possibly due to low knowledge of and insensitivity to the consequences of the practice among Nigerians. Literatures have shown that Community-based participatory education programnmes are good approaches to changing citizens‟ perceptions, knowledge and attitude about social problems. However, this approach has not been adequately used for human trafficking in Nigeria. This study, therefore, examined the effect of Community-Based Participatory Education Programme (CBPEP) on participants‟ knowledge of and attitude to human trafficking in Oyo and Osun states. Moderator effects of gender and location were also examined. The study adopted a pretest-posttest, control group, quasi-experimental design of 2x2x2 factorial matrix. One hundred and sixty participants (80 males and 80 females) were selected through cluster sampling technique in Saki (urban, 40) and Ago-Amodu (peri-urban, 40) in Oyo State and Ejigbo (urban, 40) and Masifa (peri-urban, 40) in Osun State. Participants were assigned to experimental and control groups while the treatment lasted 10 weeks. Four sessions of Focus Group Discussions (FGD) were also held with inhabitants of the four communities. Instruments used were: Human Trafficking knowledge Test (r= 0.86), Human Trafficking Attitudinal Scale (r= 0.76), Community-based participatory education programme, Direct teaching method and FGD guides. Four research questions were answered and seven null-hypotheses tested at p=0.05. Data were analysed using ANCOVA and content analysis. Treatment had a significant main effect on participants‟ knowledge (F (2,157) = 67.02 ŋ2 = .31) and attitude (F (2,157) = 17.79 ŋ2 = .02). Participants exposed to treatment had a higher human trafficking attitude mean score (=15.14) than the control group (=13.02). Gender had a significant main effect on the participants‟ knowledge (F (2,157) = 45.77 ŋ2 = .02) but not on attitude (F (2,157) = 0.89 ŋ2 = 0.01). The females had a higher knowledge of human trafficking (=60.13) than males (=50.44). The females had a higher attitudinal disposition towards human trafficking (=14.95) than the males (=13.95). Location did not have significant effect on participants‟ knowledge and attitude. Gender and location had a significant interaction effects on participants‟ knowledge (F (4,155) = 4.160 ŋ2 = 0.03) but not on attitude. The 3 way-interaction effect of treatment, gender and location was significant on participants‟ knowledge (F(8,151) = 8.415, ŋ2= .05) but not on attitude. Despite participants‟ knowledge about the consequences of human trafficking, attitudinal disposition towards the menace is still higher because of participants‟ zeal for money and the desire to live abroad. The community-based participatory education programme enhanced participants‟ knowledge of and attitude towards eradication of human trafficking and aroused the participants‟ interest in solving the problem in Oyo and Osun states. Therefore, there is the need to adopt this intervention for active participation of the people regardless of location in the process of solving human trafficking problems